Solubilization of receptors for the novel Ca2+-mobilizing messenger, nicotinic acid adenine dinucleotide phosphate. - Berridge, G; Dickinson, G; Parrington, J; Galione, A; Patel, S (2002)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a potent Ca(2+) mobilizing agent in a variety of broken and intact cell preparations. In sea urchin egg homogenates, NAADP releases Ca(2+) independently of inositol trisphosphate or ryanodine receptor activation. Little, however, is known concerning the molecular target for NAADP. Here we report for the first time solubilization of NAADP receptors from sea urchin egg homogenates. Supernatant fractions, prepared following Triton X-100 treatment, bound [(32)P]NAADP with similar affinity and selectivity as membrane preparations. Furthermore, the unusual non-dissociating nature of NAADP binding to its receptor was preserved upon solubilization. NAADP receptors could also be released into supernatant fractions upon detergent treatment of membranes prelabeled with [(32)P]NAADP. Tagged receptors prepared in this way, were readily resolved by native gel electrophoresis as a single protein target. Gel filtration and sucrose density gradient centrifugation analysis indicates that NAADP receptors are substantially smaller than inositol trisphosphate or ryanodine receptors, providing further biochemical evidence that NAADP activates a novel intracellular Ca(2+) release channel.